Artificial intelligence and software engineering understanding the promise of the future - Partridge, Derek 1945- (Glenlake Publishing Company, Ltd. ; AMACOM, American Management Association, 1998)
In this literate and easy-to-read discussion, Derek Partridge helps us understand what AI can and cannot do. Topics discussed include strengths and weaknesses of software development and engineering, the promises and problems of machine learning, expert systems and success stories, practical software through artificial intelligence, artificial intelligence and conventional software engineering problems, software engineering methodology, new paradigms for system engineering, what the future holds, and more.